The Time-Space and Identity Discourse of a City – or How to Appropriate Klaipėda? - Kiauka, Tomas (Sociologija. Mintis ir veiksmas, 2018)
In this article, two different models of Klaipėda city’s time-space appropriation are analyzed and compared by applying the phenomenological concept of “depth of time,” coined by philosopher A. Mickūnas. One is represented by a scientific-methodological discourse, examining the poetic and philosophical/publicist interpretations of the narrated city of Klaipėda; the second model includes and analyzes poetic essays on Klaipėda, which convey the artistic-aesthetic (re)presentation of the city’s time-space. This comparison allows one to draw a conclusion that artistic narration, arising from an immediate experience of the city’s time-space, appears to be a more effective form of appropriation, for it makes possible an authentic integration of different time-space dimensions, divided (and contrapositioned) by historic turning-points. Because it contains a kind of developed subjectivity, artistic narration, contrary to an approach based on academic discourse, it also has no claims to some “privileged” knowledge of the city and as such contributes to the plurality of the construction of the city’s identities.